A Novel Antimalarial Metabolite in Erythrocyte From the Hydroxylation of Dihydroartemisinin by Cunninghamella elegans - Bai, Yue; Zhao, Yifan; Gao, Xinna; Zhang, Dong; Ma, Yue; Yang, Lan; Sun, Peng (Frontiers in Chemistry, 2022)
Dihydroartemisinin (DHA) is a sesquiterpene endoperoxide with prominent antimalarial efficacy, which was discovered by Professor Youyou Tu through the reduction of artemisinin in the 1970s. It is always a challenging work for scientists to investigate the metabolites of DHA in the red blood cells due to the complicated matrix background. As a bottleneck, the investigation of metabolites, especially exploring the pharmacodynamic material in the red blood cell, is necessary and significant for metabolism research of antimalarial agent. Recently, microbial transformation provides a green and economical means for mimicking mammal metabolism and synthesis active metabolites, based on which is one efficient route for drug discovery. In this study, a strain from Cunninghamella was employed as an efficient tool to explore active metabolites of DHA in erythrocyte. Microbial transformation products of DHA by Cunninghamella elegans CICC 40250 were detected and analyzed by ultra-performance liquid chromatography (UPLC)-electrospray ionization (ESI)-quadrupole time-of-flight (Q-TOF)-mass spectrometry (MSE), and the main products were isolated and identified. The antimalarial activity of the isolated products was also screened in vitro. Totally, nine products were discovered through UPLC-ESI-QTOF-MSE, and three main products with novel chemical structures were isolated for the first time, which were also detected in red blood cells as the metabolites of DHA. After evaluation, 7β-hydroxydihydroartemisinin (M1) exhibited a good antimalarial activity with an IC50 value of 133 nM against Plasmodium falciparum (Pf.) 3D7. The structure and stereo-configuration of novel compound M1 were validated via X-ray single crystal diffraction. Microbial transformation was firstly employed as the appropriate model for metabolic simulation in erythrocyte of DHA. Three novel metabolites in erythrocyte were obtained for the first time through our microbial model, and one of which was found to show moderate antimalarial activity. This work provided a new research foundation for antimalarial drug discovery.